Youth and Drugs : Choices in life - TVE International; Ace communications (Nairobi, Kenya : Ace communications, 1990)
The preasures in life are many and varied. youth, who are in their most impressionable years experience acute peer pressure...
007
August 2006
Keywords: Drug addicts -- Rehabilitation; Youth -- Drug use